Psychological Well-Being Ditinjau dari Dukungan Sosial Pada Remaja di Pinggir Rel Kelurahan Tanjung Gusta Medan - Sri Hartini; Kelvin Tanadi; Yakub Yakub; Valerie Utami; Sri Ngayomi Yudha Wastuti (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
Psychological well-being is a condition in which one feels psychologically well, by being able to seize self-acceptance, mastery of environment, appreciation and positive meaning of life. One’s psychological well-being degree, focusing on adolescents, can be affected due to several factors, one of which is social supports they received. This study aimed to discover the relationship between social support and psychological well-being of adolescents. Correlational quantitative was used in this study, with sampled by purposive technique, namely adolescents living at railroad tracks at Tanjung Gusta Medan with age range between 13 to 18 years. Data collection tool is used by including both psychological well-being and social support scale which were arranged in the form of Likert scale. Collected data were analyzed by Pearson Product Moment Correlation, using SPSS software version 26.0 for windows. The results of this study showed an effective contribution at 54,7 percent and correlation coefficient of 0.739. In another word, both variables are positively related. High social support will increase the one’s psychological well-being degree, whereas low social support will hinder their psychological well-being degree.